1992
DOI: 10.1093/oxfordjournals.ndt.a092130
|View full text |Cite
|
Sign up to set email alerts
|

Functional endothelin 1 receptors on human glomerular podocytes and mesangial cells

Abstract: To determine if endothelin 1 (Et1) receptors are present in human glomeruli, and which glomerular cells possess these receptors, 125I Et1 binding to isolated glomeruli and cultured glomerular mesangial and epithelial cells was studied. The latter were identified as podocytes. We demonstrated that Et1 binds specifically and reversibly to isolated human glomeruli and to cultured glomerular mesangial and epithelial cells. Scatchard analysis of competitive inhibition of 125I Et1 binding gave the following results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The presence of AT-1-subtype receptors for Ang II is illustrated by studies in podocyte cultures where Ang II depolarised podocytes [40]. Additionally, functional ET-1 receptors had been also found on podocytes [41].…”
Section: Discussionmentioning
confidence: 97%
“…The presence of AT-1-subtype receptors for Ang II is illustrated by studies in podocyte cultures where Ang II depolarised podocytes [40]. Additionally, functional ET-1 receptors had been also found on podocytes [41].…”
Section: Discussionmentioning
confidence: 97%
“…Several other agonists have been reported to modulate [Ca 2ϩ ] i in podocytes (19,35,121,159,176,313,348,349,363,422,(441)(442)(443). Table 1 summarizes the respective hormones and their receptors, which have been detected in podocytes in vitro and in vivo.…”
Section: Ca 2؉ Signalingmentioning
confidence: 99%
“…We also determined the effects of darusentan treatment for glomerular gene expression in vivo of matrix metalloproteinase-9 (MMP-9), which is involved in glomerular matrix turnover. 5 MMP-9 gene expression was determined in laser-dissected glomeruli of the study animals and was found to be reduced by 65% after darusentan treatment (from 6.0 [2.8] to 2.1[1.6] units; nϭ10 per group; Pϭ0.0015; Figure 5a) Because stability and function of podocytes were improved after darusentan treatment in vivo and regulation of calcium signaling by endothelin 15 suggests that podocytes are functional targets of ET-1, we set out experiments to investigate the role of endogenous and exogenous endothelin in an in vitro podocyte injury model. Endothelin receptor expression of both endothelin receptor subtypes was present in human podocytes (Ortmann and Barton, unpublished observation, 2004), and MMP-9 gene expression and cytoskeletal disruption were chosen as a read-outs of podocyte injury as described previously.…”
Section: Ortmann Et Al Pedocytes and Reversal Of Renal Aging 977mentioning
confidence: 99%
“…12 As we have shown previously, ET-1 expression increases in the aging kidney in the absence of other risk factors. 13,14 Because podocytes are targets of ET-1, 15 we sought to investigate the effects of treatment with an orally active ET A receptor antagonist on renal structure and function in aged rats with established glomerulosclerosis and podocyte injury.…”
mentioning
confidence: 99%